The role of social media in reshaping the academic activities of vocational and technical education lecturers in Nigeria - Adamu Muhammaed Jebba (Institute of Advanced Engineering and Science, 2019)
The use of social media is one of the predominant features in the average daily life of students and lecturers across tertiary institutions in Nigeria. It was against this backdrop that this study was carried out to determine the role of social media in reshaping the future of academic activities among lecturers of Vocational and Technical education in Nigeria. The study adopted descriptive survey research design. A structured questionnaire consisting of 40- items was developed by the researcher for data collection. The reliability of the instrument was determined using Kuder Richardson (KR20) formula which yielded 0.85. The population of the study comprised lecturers from the two Colleges of Education in Niger State. Four research questions guided the study. The findings revealed among others that social media is a technological tool that can reshape the future of teaching Vocational and Technical education as it brings with it new opportunities which is capable of promoting collaborative teaching and learning as well as the potential to promote and reshape the future of higher education in institutions of learning. Furthermore, the trend according to the findings of this study revealed that the overwhelming patronage is in terms of making new friends (online), playing games, exchange of affectionate/love messages, online chatting, sharing selfies, spreading false information, hate speeches, and even quarrelling with virtual friends. On the basis of these findings, some recommendations were made which among others include the need for the college management to mount capacity building programmes to retrain the lecturers to understand the concept of social learning and to keep them abreast with innovative teaching and learning platform such as social media.